2008
DOI: 10.1016/j.ejvs.2007.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Heparin Treatment Decreases MMP-9 Plasma Activity in Patients with Abdominal Aortic Aneurysm

Abstract: Large abdominal aortic aneurysms (AAAs) are associated with coagulation abnormalities, which are significantly reduced by low molecular weight heparin (LMWH). Considering anti-inflammatory properties of heparin we verified, whether LMWH influences MMP-2/-9 in AAA patients. The study involved 26 AAA individuals, 10 patients with coagulation abnormalities received LMWH and 16 were a control group. The plasma activity of MMP-2/-9 was measured using zymography. We found that, in addition to the reduction of coagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…8,9,[82][83][84][85] Some authors have postulated the complex indirect inhibitory influence of heparin and GAG-sulodexide on MMPs (revealed especially by low-molecular-weight heparin fraction). 12,82 However, there are also data suggesting direct inhibitory properties of dermatan sulfate fraction in sulodexide. 7,84 Recently, the role of interaction between MMPs and endogenous GAGs was postulated as the important mechanism in the development of vascular pathologies, especially chronic venous disease and venous leg ulcers.…”
Section: Heparin and Glycosaminoglycansmentioning
confidence: 99%
“…8,9,[82][83][84][85] Some authors have postulated the complex indirect inhibitory influence of heparin and GAG-sulodexide on MMPs (revealed especially by low-molecular-weight heparin fraction). 12,82 However, there are also data suggesting direct inhibitory properties of dermatan sulfate fraction in sulodexide. 7,84 Recently, the role of interaction between MMPs and endogenous GAGs was postulated as the important mechanism in the development of vascular pathologies, especially chronic venous disease and venous leg ulcers.…”
Section: Heparin and Glycosaminoglycansmentioning
confidence: 99%
“…Furthermore, recent data have shown that treatment with a low-molecular-weight heparin decreases the levels of MMP-9 in patients with abdominal aortic aneurysm [184]. Again, angiotensin converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (AIIRBs) reduce the raised circulating MMP-9 levels in patients with stable coronary artery disease [185], and the levels of this enzyme are also reduced by ACEI captopril in patients with acute myocardial infarction [186].…”
Section: Inhibition Of Metalloproteinases As Therapeutic Strategies Fmentioning
confidence: 99%
“…Finally, heparin inhibits in vitro the expression and activity of some MMPs in smooth muscle cells [76], and recent data show that treatment with a low-molecular heparin decreases the raised plasma levels of MMP-9 in patients with AAA [77]. New selective approaches to MMP-inhibition are in development [29], and only their future application to clinical conditions associated with atherothrombosis, and in particular to PAD, will clarify conclusively the importance of MMPs in atherothrombosis.…”
Section: Mmps and Diabetesmentioning
confidence: 99%